Ozone treatment of wastewater sludge for reduction and stabilization - Park, K. Y.; Maeng, S. K.; Song, K. G.; Ahn, K. H. (TAYLOR & FRANCIS INC, 2008)
Ozonation was applied to wastewater sludge for reduction and stabilization. Ozone was found to be very effective at reducing sludge and producing a useful carbon source. An ozone dose of 0.3 g/gDS fulfilled the criteria for the disinfection of class A type biosolids. The sludge treated with 0.5 gO(3)/gDS produced no hydrogen sulfide for a month at 29 degrees C. Ozonation resulted in low pH conditions, which might facilitate the mobilization of heavy metals from sludge. The results of a geotechnical investigation proved that the residuals of ozone-treated sludge did not meet the required properties required for landfill cover without the addition of quick lime.
Keywords: DIGESTED SEWAGE-SLUDGE; ANAEROBIC-DIGESTION; DISINTEGRATION